Methane production as key to the greenhouse gas budget of thawing permafrost - Knoblauch, Christian; Beer, Christian; Liebner, Susanne (Jun.-Prof. Dr.); Grigoriev, Mikhail N.; Pfeiffer, Eva-Maria (Nature Climate Change, 2018)
Permafrost thaw liberates frozen organic carbon, which is decomposed into carbon dioxide (CO2) and methane (CH4). The release of these greenhouse gases (GHGs) forms a positive feedback to atmospheric CO2 and CH4 concentrations and accelerates climate change(1,2). Current studies report a minor importance of CH4 production in water-saturated (anoxic) permafrost soils(3-6) and a stronger permafrost carbon-climate feedback from drained (oxic) soils(1,7). Here we show through seven-year laboratory incubations that equal amounts of CO2 and CH4 are formed in thawing permafrost under anoxic conditions after stable CH4-producing microbial communities have established. Less permafrost carbon was mineralized under anoxic conditions but more CO2-carbon equivalents (CO2Ce) were formed than under oxic conditions when the higher global warming potential (GWP) of CH4 is taken into account(8). A model of organic carbon decomposition, calibrated with the observed decomposition data, predicts a higher loss of permafrost carbon under oxic conditions (113 +/- 58 g CO2-C kgC(-1) (kgC, kilograms of carbon)) by 2100, but a twice as high production of CO2-Ce (241 +/- 138 g CO2-Ce kgC(-1)) under anoxic conditions. These findings challenge the view of a stronger permafrost carbon-climate feedback from drained soils1,7 and emphasize the importance of CH4 production in thawing permafrost on climate-relevant timescales.